Was King David an Exorcist? - Biegas, Marcin (The Biblical Annals, 2023)
This article analyses the image of David as an exorcist. The choice of the research topic has been inspired by the fact that in the literature, more specifically, in an article by Kenneth E. Pomykala, this issue is presented in a very general way, by indicating only texts where such an image of David can be found, without entering into their deeper interpretations. Also, no scientific article covering this topic in detail has been published to date. The paper is divided into three parts. The first part presents biblical texts in which – as Pomykala has proven – one can talk about this characteristic of David. In the second part, fragments of two Qumran manuscripts, 11Q5 and 11Q11, are analysed. Finally, an analysis of the literaturę of early Jewish writings, portraying David as an exorcist, is provided.